Damage classification in reinforced concrete beam by acoustic emission signal analysis - Shahidan, Shahiron (2014)
Structural health monitoring (SHM) is known as assessment on damage detection in structural engineering. Nowadays, the application of SHM has been widely used especially on the continuous real time monitoring system with minimum labour involvement. One of the most excellent tools in SHM for real time monitoring system is Acoustic emission (AE). AE waves are high frequency stress wave generated by rapid release of energy from localised sources with a material, such as crack initiation and growth. High sensitivity to crack growth, the ability to locate source, passive nature and the possibility to perform real time monitoring are some of the attractive features of AE technique. In spite of these advantages, challenges still exist in using AE technique for monitoring applications especially in analysing recorded AE data as large volume of data are usually generated during monitoring. The need for effective data analysis in grading system can be linked into the three main objective of this research; (a) determine the grading system; (b) identify and discriminate the AE data parameter ; (c) and validate a new standard grading system for severity assessment. In this research, cyclic load test (CLT) method is the first method used for this evaluation system. This is a relatively new method that may provide a good insight into structural integrity status and also collaborates with the AE evaluation system. In the evaluation of AE data parameters, the conventional method known as parameter analysis (PA) was used to evaluate the reinforced concrete (RC) structure. This study has proposed and tested the absolute energy parameter in the evaluation for determining the damage level in RC structure. In addition, the cracks patterns in RC beam have been identified according to the type of cracking process and the cracks classifications by using the AE data parameters mainly AE amplitude, rise time, and average frequency. These data parameters have been analysed by using the statistical methods of b-value and RA value analysis. Quantification tool to assess the severity of the damage is extensively described in the practice applications. Even though different damage quantification methods have been proposed in AE technique, not all achieved universal approval or suitable for all situations. The IEA and ISA methods that involved the absolute energy and signal strength parameter were investigated for determining the damage level in RC structure. This was found to provide encouraging result for the analysis of AE data parameters in determining the damage grading system. By addressing this primary issue, it is believed that this thesis has helped to improve the effectiveness of AE technique for SHM in civil engineering.